Maximal oxygen consumption predicts skeletal and heart muscle biomarkers changes after a full distance Ironman - Danielsson, T.; Bergman, P.; Carlsson, J. (19:e Kardiovaskulära Vårmötet 2017, 2017)
Strenuous exercise like marathon or triathlon leads to disturbances of several biomarkers, not at least markers of skeletal and heart muscle damage. Different predictors of biomarker changes, e.g. sex, age and training experience have been discussed in the literature with contradictory results. To our best knowledge, maximal oxygen consumption (VO2 max) has not been investigated in this setting.